Religious vocabulary and biblical allusions in english language teaching: contemporary challenges, students’ needs, and the prospects of corpus-informed instruction - Haiduk, Hanna (Запоріжжя: ТДАТУ, 2026)
The integration of religious vocabulary and biblical allusions into English Language Teaching (ELT) presents a multifaceted challenge in contemporary educational contexts. While English remains deeply rooted in Judeo-Christian traditions, modern classrooms are increasingly diverse, requiring pedagogical approaches that balance cultural literacy with inclusivity. The findings from corpus analysis of the Biblical English Corpus (BEC) and the Corpus of Contemporary American English (COCA) provide a robust empirical foundation for understanding the linguistic behaviour of religious vocabulary and its relevance for language instruction. These findings not only confirm the quantitative and functional significance of religious lexis but also illuminate how corpus-informed methodologies can enhance teaching practices.
Keywords: religious vocabulary; English Language Teaching